A proteomic and functional view of intrabacterial lipid inclusion biogenesis in mycobacteria - Tonia Dargham; John Jairo Aguilera-Correa; Romain Avellan; Ivy Mallick; Léa Celik; Pierre Santucci; Gael Brasseur; Isabelle Poncin; Vanessa Point; Stéphane Audebert; Luc Camoin; Wassim Daher; et al. (mBio)
ABSTRACT During infection and granuloma formation, pathogenic mycobacteria store triacylglycerol as intrabacterial lipid inclusions (ILIs). This accumulation of nutrients provides a carbon source for bacterial persistence and slows down intracellular metabolism. Mycobacterium abscessus (Mab), a rapidly growing non-tuberculous actinobacterium, produces ILI throughout its infection cycle. Here, Mab was used as a model organism to identify proteins associated with ILI accumulation on a global scale. By using the APEX2 proximity labeling method in an in vitro model for ILI accumulation, we identified 228 proteins possibly implicated in ILI biosynthesis. Fluorescence microscopy of strains overexpressing eight ILI-associated proteins (IAP) candidates fused to superfolder green fluorescent protein showed co-localization with ILI. Genetic inactivation of these potential IAP-encoding genes and subsequent lipid analysis emphasized the importance of MAB_3486 and MAB_4532c as key enzymes influencing triacylglycerol storage. This study underscores the dynamic process of ILI biogenesis and advances our understanding of lipid metabolism in pathogenic mycobacteria. Identifying major IAP in lipid accumulation offers new therapeutic perspectives to control the growth and persistence of pathogenic mycobacteria.IMPORTANCEThis study sheds light into the complex process of intracellular lipid accumulation and storage in the survival and persistence of pathogenic mycobacteria, which is of clinical relevance. By identifying the proteins involved in the formation of intrabacterial lipid inclusions and revealing their impact on lipid metabolism, our data may lead to the development of new therapeutic strategies to target and control pathogenic mycobacteria, potentially improving outcomes for patients with mycobacterial infections.